Beyond well-being : spirituality and human flourishing - Miner, Maureen; Dowson, Martin; Devenish, Stuart (Emerald Publishing Limited : Information Age Pulishing, 2012)
This volume arose out of a deep concern to assist people in their struggle to lead a flourishing life. Fractured, stressed, relationally broken and spiritually empty people may instinctively reach for the supposed panacea of happiness. But happiness is often a transitory state. More stable and worthwhile than the pursuit of happiness is leading a flourishing life. But what is flourishing? Is spirituality necessary for human flourishing and, if so, in what ways might spirituality provide a unique and important contribution to flourishing?The volume provides complementary yet diverse accounts of human flourishing. Each account argues that spirituality in general, and Christian spirituality in particular, are vital contributors to flourishing.The volume will be valuable for those who are dissatisfied with popular hedonistic approaches to flourishing. Such people are ready for a change in approach, but often do not have a clear alternative in view. The Volume will provide a clear alternative to popular culture's representation of the flourishing person, which is largely vested in conspicuous consumption. The book will also be valuable for those who have considered alternatives to popular culture, but who lack an informed basis on which to evaluate these alternatives. Finally, the book will be valuable for those who are committed to Christian spirituality but may not appreciate the rich resources which Christian faith offers for human flourishing. Amongst the latter group are included Christian leaders such as priests and pastors, voluntary church workers and lay people who may or may not be involved in formal religion but who long to flourish in their own lives and to enable others to do the same.